(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the effect of biochar and mineral fertilizers on the morphological indicators of the root system in okra plants was studied. It was determined that the total root length, root diameter, root surface area, and root volume of okra plant were increased the highest by treatments using combination with biochar and mineral fertilizers.